Bronze John Steinbeck statue in Monterey - Steven Domingo:::Photographer:::::::::::: (Monterey, California, 2024)
A close up photograph of the bronze John Steinbeck that sits atop the Cannery Row Monument in Monterey, California. The monument was created by sculptor Steven Whyte under the direction of Mr. Ted Balestreri. For more information see: https://www.innsofmonterey.com/blog/the-cannery-row-monument